Estudo do potencial climático para cana-de-açúcar (Sacharum ssp.) no Rio Grande do Sul por meio de geoprocessamento: estudo de caso no município de Jaguari - Soares, Fernando Uhlmann (2008)
This work approaches an agro climatic zoning for the sugar cane crop (Sacharum ssp.) in the State of the Rio Grande do Sul Brazil through techniques of geoprocessing. The study was organized in thematic chapters including, in first, all municipalities of the State and, in a second moment, a rectangle centered in the municipality of Jaguari, main producer of region central. The Brazilian production and the production of the world were discussed since an historical point of view by means of the spatial analysis of thematic maps. The risk of frost in Jaguari region was evaluated considering the minimum temperature of five meteorological stations, with more than 25 years of daily records. Several farms of sugar cane in the municipality of Jaguari were located with global position system at field. These farms were used as pilot areas in satellite imagery for classification of the use of land. Thus, the present work results a useful instrument for the planning the harvest of sugar cane crop because of the reduction of risk of frost. Therefore, the study intends to guide the public and private politics about the production of sugar cane in Rio Grande do Sul State. Finally, it might be suggested that Geographic Information Systems (GIS) is a potential tool for this kind of study.